Post-glacial climatic change on Boothia Peninsula, Nunavut, Canada - Zabenskie, Susan (University of Ottawa (Canada), 2006)
A high temporal resolution pollen diagram from a lake in the middle-Arctic region of the Boothia Peninsula, Nunavut, Canada, documents the history of the regional vegetation and climate for the past 7200 years. A diatom sequence had been previously prepared from this core. Major tundra pollen taxa in the core include Cyperaceae and Salix, with Cyperaceae comprising over 50% of the pollen in the early and late Holocene. Tree pollen, transported from far to the south, comprised a large percentage of the pollen sum, with Pinus accounting for 30% of the pollen in some levels of the core. Pollen percentages and concentrations of taxa typical of the middle-Arctic were highest in the mid-Holocene, corresponding to warm conditions. Decreasing pollen concentrations indicate cooling temperatures, with more rapid decreases occurring around 4200, 3800-3400, and 2500 cal yr BP. Pollen percentages of Salix, Cyperaceae, and Artemisia increased in the past 35 years in response to global warming. Reconstructions of July temperature using the modern analog technique showed the mid-Holocene (5800-2800 cal yr BP) was approximately 1°C higher than during the past 1000 years.
Keywords: Physical Geography.; Paleontology.